(untitled) (Physical Education, Health and Social Sciences, 2026)
Corporate sustainability reporting is evolving from being primarily voluntary to the frameworks that are increasingly mandated and prescriptive. This transition has exacerbated apprehensions of the disclosure quality, selective reporting and the ESG assertions’ veracity. In this conceptual paper, a multi-level framework is developed to explain when and how board gender diversity shapes CSR disclosure outcomes under different reporting architectures. By integrating tokenism and critical mass theory with institutional theory and the economics of disclosure regulation, we contend that board gender diversity functions through a mechanism of a threshold. Governance influence is most likely to change qualitatively once the boards reach the point of critical mass of women directors, in which token constraints are reduced and influence capacity increases through stronger monitoring and agenda setting. We conceptualised voluntary and mandatory reporting regimes as discretion structures in this study. These structures determine whether the quality of the disclosure and also the credibility are primarily governance-driven or compliance-driven. Under the voluntary regimes, boards retain latitude over disclosure scope, specificity, and credibility investments, which makes critical mass effects more visible in observed disclosure outcomes. Under mandatory regimes, standardised requirements can raise disclosure floors and comparability; however, they can also compress cross-firm variance. Such regimes can attenuate the marginal association between board critical mass and measured disclosure quality, even when the governance is internally improved. In this framework two CSR-related outcomes are differentiated, which are the quality of CSR disclosure and the disclosure of credibility investments. We emphasised external assurance as a salient credibility mechanism, noting that its adoption depends on board influence capacity and the availability of verification infrastructure. We develop propositions and boundary conditions which include enforcement intensity, liability exposure, informal stakeholder pressures, institutional complexity, industry ESG salience, ownership structures, political embeddedness, and the maturity of assurance markets. The paper contributes by reconciling mixed findings in the governance and CSR disclosure literature. It clarifies when board composition should matter most. It also outlines an empirical research agenda for testing regime-contingent critical mass effects in evolving sustainability reporting systems.